Comparative Analysis of Cloud Storage Architectures for Scalability and Security - Fitri Nurdianingsih; Wahyu Nur Wahid; Jonathan Parker (IAIC Bangun Bangsa, 2026)
This study compares the scalability and security of the InterPlanetary File System (IPFS) and traditional cloud storage platforms. As global data traffic continues to rise, traditional centralized cloud services, like AWS S3 and Google Cloud Storage, face increasing challenges in terms of scalability, security, and data sovereignty. In contrast, IPFS offers a decentralized, content-addressed storage model that enhances data integrity and resilience. This research uses a combination of qualitative and quantitative methods, including a literature review, performance benchmarking, and security assessments. The evaluation involved testing various file sizes, monitoring data availability over seven days, and conducting fault tolerance simulations. The findings reveal that traditional cloud platforms provide stable, predictable performance, low latency, and high availability, making them suitable for enterprise applications. However, IPFS, with its decentralized architecture, excels in ensuring data integrity and resilience in distributed environments, although it experiences performance variability and lacks built-in encryption and access control. These factors make IPFS less viable in regulated settings. The study concludes that IPFS and traditional cloud storage should not be seen as alternatives, but as complementary systems. A hybrid approach, combining the strengths of both, can support scalable, secure, and sustainable digital infrastructures, aligning with SDG 9, which promotes innovation and resilient infrastructure development